Latinos in the American political system : an encyclopedia of Latinos as voters, candidates, and office holders - Lavariega Monforti, Jessica (ABC-CLIO, 2019)
This encyclopedia provides a comprehensive overview of the evolution of Hispanic American engagement in U.S. politics, from their increased visibility as governors and other lawmakers at the local, state, and federal levels to their growing importance as a voting constituency.